Effects of brining process on nutrient composition of fish species (kharo, govazim and kijar) from Iran (International Journal of Agricultural Research, Innovation and Technology, 2015)
This research work was directed on the study of the proximate chemical composition to compare the effect of the brining constant concentration and different times on the nutritive value of fish. The proximate composition of treated Chirocentrus nudus (protein, fat, ash and energetic value) for 8% salt and 18 h brining was 61.2%, 15.2%, 23.2% and 381.60 kcal/100g respectively. Fat and ash contents in brined fillets of Nemipterus japonicus and Saurida tumbil were found lower and more than C. nudus respectively. As for the proximate composition of C. nudus, it is clearly observed that all the studied parameters are significantly different in fresh and treated samples. Variations appeared in nutrients was due to the interaction of the salting treatment. It is concluded that fish treated C. nudus was best option.Int. J. Agril. Res. Innov. & Tech. 5 (1): 36-39, June, 2015